LEGAL ISSUES ON INDONESIAN MARINE PLASTIC DEBRIS POLLUTION - Jing, Zhen; Sutikno, Sutikno (UI Scholars Hub, 2020)
Various problems related to marine plastic debris pollution have yet to be resolved. Therefore, the definition, categorization, origin, and degradation of marine plastic debris must be thoroughly investigated to gain a comprehensive understanding of the related issues. The presence of marine plastic debris has significant implications on marine environments, including ecological, biodiversity, health, and economic impacts. Marine plastic debris originates from both landand ocean-based sources, and there have been efforts to prevent or reduce its introduction and accumulation in the marine environment. In Indonesia, such a problem must be solved through the implementation of more effective, efficient, and specific regulations, especially because it is the second-largest contributor of plastic debris in the marine environments throughout the world. In order to reduce 70% of such debris by 2025, the Government of Indonesia established the National Coordination Team of Marine Debris Management, which is tasked to draft policies and carry out coordination, control, and evaluation related to marine plastic debris pollution. The law enforcement in marine plastic debris pollution is known as the legal system, which comprises the substance of the law, facilities, society and culture, and the officers enforcing the law. The effectiveness of law enforcement refers to the ideal combination of these aforementioned elements.